The Development of An Interactive Biology E-Module Based on Articulate Storyline for Class XI Digestive System Concepts - Fajar Riyanto; Sujiyo Miranto; Meiry Fadilah Noor (International Journal of Learning Media on Natural Science (IJLENS), 2024)
This research aims to develop interactive learning media based on Articulate Storyline for the digestive system concept in class XI and to determine students' responses to the media development outcomes. The research method used is Research and Development (RnD)with the ADDIE development model, namely Analyze, Design, Development, Implementation, and Evaluate, but it was only carried out up to the development stage. The media development stage underwent a validation process by media and material experts, resulting in an average material validation percentage of 84.33% with excellent criteria. Meanwhile, the media validators reported an average percentage of 89%, also with excellent criteria. The media was tested on students of class XI at SMA Negeri 95 Jakarta Barat, withthe trial showing positive results. The percentage of response results averaged 90.90% with excellent criteria. Based on these results, the use of interactive e-modules based on Articulate Storyline can meet the needs of students as supplementary learning media for thedigestive system concept.